Computer Modeling of the Process for Manufacturing Spherical Vessels from Sheet Steel by Hydroforming - Pavlo P. Hontarovskyi; Natalia V. Smetankina; Nataliia H. Garmash; Iryna I. Melezhyk; Tetiana V. Protasova (Journal of Mechanical Engineering)
Reliable and safe operation of vessels filled with gas or liquid under high pressure requires compliance with certain requirements for their strength. It is also important to reduce weight and material consumption. Numerous industries, including automotive, chemical engineering, and the rocket and space industry, which supply products in bulk, effectively use hydroforming technology for the manufacture of components. Hydroforming is a metalworking process in which complex-shaped structures are created using fluid pressure and displacement constraints instead of traditional mechanical loads (or in combination with them). The successful implementation of this technology is possible due to the advantages that hydroforming has compared to traditional methods, such as the assembly of blankings by welding. A simulation of the manufacture of spherical vessels from sheet steel by hydroforming is proposed in this paper. The software developed on the basis of the finite element method is used, which allows solving elastoplastic problems of thermomechanics by time or load steps in combination with an iterative process on each of them, during which the geometry of the deformed part is refined. To describe the stress-strain state, a logarithmic measure of deformations is used, which allows reflecting real processes occurring in the workpiece. Plastic deformations are taken into account using deformation theory. Thanks to computer modeling of hydroforming technology, spherical models that have the lowest metal content at high pressure were obtained. The obtained vessel models deform elastically under repeated loading due to an increase in the yield strength of the material, therefore they will not be damaged by low-cycle fatigue. They can be used in aerospace engineering as fuel tanks for liquefied oxygen or fluorine and hydrogen. Computer modeling of the hydroforming process allows to quickly and cheaply set the parameters of vessels of various sizes and from different materials, and to obtain an acceptable result without resorting to multiple experimental attempts.